Principles of Microeconomics Scarcity and Social Provisioning - Dean, Erik; Elardo, Justin; Green, Mitch; Wilson, Benjamin; Berger, Sebastian; Open Textbook Library (Open Textbook Library, 2016)
Principles of Microeconomics: Scarcity and Social Provisioning takes a pluralistic approach to the standard topics of an introductory microeconomics course. The text builds on the chiefly neoclassical material of the OpenStax Principles of Economics text, adding extensive content from heterodox economic thought. Emphasizing the importance of pluralism and critical thinking, the text presents the method and theory of neoclassical economics alongside critiques thereof and heterodox alternatives in both method and theory. This approach is taken from the outset of the text, where contrasting definitions of economics are discussed in the context of the various ways in which neoclassical and heterodox economists study the subject. The same approach-of theory and method, critique, and alternative theory theory and method-is taken in the study of consumption, production, and market exchange, as well as in the applied theory chapters. Historical and contemporary examples are given throughout, and both theory and application are presented with a balanced approach. This textbook will be of interest especially to instructors and students who wish to go beyond the traditional approach to the fundamentals of microeconomic theory, and explore the wider spectrum of economic thought. Instructors may contact Open Oregon Educational Resources for quiz question test banks associated with each chapter.
Chapter 1. Welcome to Economics! -- Chapter 2. Choice in a World of Scarcity -- Chapter 3: Defining Economics: A Pluralistic Approach -- Chapter 4. Demand and Supply -- Chapter 5. Labor and Financial Markets -- Chapter 6. Elasticity -- Chapter 7. Consumer Choices -- Chapter 8. Challenging the Role of Utilitarianism -- Chapter 9. An Institutional Analysis of Modern Consumption -- Chapter 10. Cost and Industry Structure -- Chapter 11. Perfect Competition -- Chapter 12. Monopoly -- Chapter 13. Monopolistic Competition and Oligopoly -- Chapter 14. The Rise of Big Business -- Chapter 15. Costs and Prices: The Evidence -- Chapter 16. The Megacorp -- Chapter 17. Monopoly and Antitrust Policy -- Chapter 18. Environmental Protection and Negative Externalities -- Chapter 19. Positive Externalities and Public Goods -- Chapter 20. Poverty and Economic Inequality -- Chapter 21. Issues in Labor Markets: Unions, Discrimination, Immigration -- Chapter 22. Information, Risk, and Insurance -- Chapter 23. Financial Markets -- Chapter 24. Public Economy -- Chapter 25. Money and the Theory of the Firm -- Chapter 26. International Trade -- Chapter 27. Globalization and Protectionism -- Chapter 28. The Economics of Globalization and Trade: A Pluralistic Approach
In English.
Description based on online resource
Keywords: Economics -- Textbooks